2006
DOI: 10.1002/macp.200690004
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Macromol. Chem. Phys. 4/2006

Abstract: Cover: Time-efficient quantification of very low branch content in polyethylene using optimised melt-state 13 C NMR under magicangle spinning. Concentrations of 7-8 branches per 100 000 CH 2 groups were determined in only 13 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 0 publications
0
55
0
Order By: Relevance
“…An early study was reported by Hatfield et al using a 200 MHz spectrometer ( 1 H resonance), [34,35] followed by intensive works of Wilhelm, Kaminsky and their co-workers. [33,36,37] Compared (5 of 20) 1600012 to the solution NMR, which has a sample concentration less than 20 wt%, the melt and solid-state 13 C NMR generate a higher sample filling factor, resulting in a higher sensitivity towards the presence of sparsely branched side chains and end groups in POs. This technique currently allows the characterization of branch lengths up to 16 carbons.…”
Section: Ch(b ) Ch(b )mentioning
confidence: 99%
See 1 more Smart Citation
“…An early study was reported by Hatfield et al using a 200 MHz spectrometer ( 1 H resonance), [34,35] followed by intensive works of Wilhelm, Kaminsky and their co-workers. [33,36,37] Compared (5 of 20) 1600012 to the solution NMR, which has a sample concentration less than 20 wt%, the melt and solid-state 13 C NMR generate a higher sample filling factor, resulting in a higher sensitivity towards the presence of sparsely branched side chains and end groups in POs. This technique currently allows the characterization of branch lengths up to 16 carbons.…”
Section: Ch(b ) Ch(b )mentioning
confidence: 99%
“…[37] In addition, the measurement acquisition times are greatly reduced. LCBD of 7-8 branches per 100 000 CH 2 groups can be determined by melt-state NMR in 13 h, [36] which represents a vast improvement over the multiday acquisitions required for the solution NMR.…”
Section: Ch(b ) Ch(b )mentioning
confidence: 99%
“…n c stands for the molar comonomer content determined from melt-state NMR spectroscopy. [33,34] Results and Discussion…”
Section: Samplesmentioning
confidence: 99%
“…Here T C 1 values of branches containing six and more carbons were determined using an optimised melt-state MAS NMR method [15,16] allowing rapid determination of relaxation parameters.…”
Section: Full Papermentioning
confidence: 99%
“…For further details of the optimised melt-state MAS method the reader is directed to the literature. [15,21,22] Melt-state spin-lattice relaxation times were measured using both inversion-recovery and saturation-recovery experiments. A combination of 16 dummy scans and 64 real scans were used per t 1 delay to compensate for NOE and saturation effects.…”
Section: Experimental Partmentioning
confidence: 99%